1997
DOI: 10.1038/sj.ijo.0800373
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors in relation to weight change among men and women from two southeastern New England communities

Abstract: OBJECTIVE: Dietary factors, independent of total energy, may be important in promoting obesity. We examined prospectively the relationship between baseline diet composition and weight gain among adult men and women from southeastern New England. DESIGN: The prospective association of nutrient consumption and weight change was examined in a randomly selected cohort examined four years apart. SUBJECTS: Adults aged 18 through 64 years from two communities in Southeastern New England were randomly selected for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
4
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 34 publications
4
65
4
1
Order By: Relevance
“…There are three studies showing no association. 3,20,21 Two studies show direct relations, 10,11 one among men, the other in both genders, but only with regard to sports activity. In three studies, the expected inverse relation 11,22,23 was found, the two of them in women only, and the third study without adjustment for baseline BMI, which implies that the observed effect could also be a result of the effect of BMI on physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…There are three studies showing no association. 3,20,21 Two studies show direct relations, 10,11 one among men, the other in both genders, but only with regard to sports activity. In three studies, the expected inverse relation 11,22,23 was found, the two of them in women only, and the third study without adjustment for baseline BMI, which implies that the observed effect could also be a result of the effect of BMI on physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The law of energy balance dictates that an energy intake that exceeds energy needs will contribute towards weight gain. Indeed, several observational studies have shown an increase of BMI with increasing energy intake (Parker et al, 1997;Gillis et al, 2002;Schroder et al, 2003). Furthermore, experimental studies found an increase of total energy intake with higher energy density of the diets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obesity is generally considered as an aesthetic drawback in most modern societies. Reduced energy intake and increased physical activity are the only established approaches to reducing BMI that can be sustained over long periods of time (Klesges et al, 1992;Nelson & Tucker, 1996;Rising et al, 1994;Schulz & Schoeller, 1994;De Groot & van Staveren, 1995;Parker et al, 1997;Trichopoulou et al, 2000). There is also an extensive literature, from both animal experiments and human studies, addressing the question whether specific energy-generating nutrients affect BMI differentially, after accounting for their energy content (Slattery et al, 1992;Stubbs et al, 1997;Willett, 1998a;West & York, 1998).…”
Section: Introductionmentioning
confidence: 99%